PENGARUH TEKANAN EKSTERNAL, FINANCIAL STABILITY, AUDIT OPINION, DAN INEFFECTIVE MONITORING TERHADAP KECURANGAN LAPORAN KEUANGAN - Mutiarani, Adiea Marita; Shanti, Yunita Kurnia (LPPM Universitas Ibnu Sina, 2025)
This study aims to determine and examine the effect of external pressure, financial stability, audit opinion, and ineffective monitoring on financial statement fraud. The type of research used in this study is quantitative using secondary data. The population of this study is a State-Owned Enterprise (BUMN) company listed on the Indonesia Stock Exchange for the period 2017-2022. The number of samples obtained using purposive sampling technique was 17 companies with observations for 6 years, obtained a total of 102 observations of company data and analyzed using panel data regression techniques with common effect models to test the hypothesis. Hypothesis testing in this study uses panel data regression using E-views software version 10. The results of this study indicate that external pressure, financial stability, audit opinion and ineffective monitoring simultaneously affect financial statement fraud. External pressure partially has a significant positive effect on fraudulent financial statements. While financial stability, audit opinion, and ineffective monitoring partially have no effect on financial statement fraud.